Can Functional Connectivity at Resting Brain in ADHD Indicate the Impairments in Sensory-Motor Functions and Face/Emotion Recognition? - Icer, Semra; Benli, Serife Gengec; Gumus, Kazim; Demirci, Esra; Ozmen, Sevgi; Doganay, Selim (Journal of medical and biological engineering, 2018)
Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disease known to cause impairments in cognitive, sensory-motor functions and face/emotion recognition. This study aimed to examine the resting-state brain networks in children with ADHD using functional magnetic resonance imaging. We performed seed-to-voxel and region of interest (ROI) analyses including all Broadmann areas (BAs) comprehensively. Thirty right-handed children aged between 9 and 16 years (15 with ADHD and 15 typically developing control subjects closely matched for age and gender) were included. Ninety five brain regions including 84 BAs and 11 Default Mode network (DMN)-related regions (rsREL) were studied using seed-based and ROI-to-ROI analysis and connectivity measures were calculated (p < 0.001). Between-group differences were assessed by using t-statistics (p < 0.05). Seed-based analysis showed connectivity differences in the sensory-motor and face/emotion recognition regions in both groups. The between-group whole-brain comparison showed greater magnitude of activation in children with ADHD than in control subjects in brain regions that included the face/emotion recognition system and prefrontal cortex based on ROI-to-ROI analysis. This work revealed that the sensory-motor regions and regions related to face/emotion recognition showed atypical functional connectivities in ADHD patients compared to the controls. Observation of the differences in these regions supports previous findings in the literature based on task-based functional magnetic resonance imaging (fMRI) studies. Our study exhibited that these atypical differences can also occur in the resting brain. These results suggest that further investigations of regions related to motor-sensory and face/emotion recognition are required to better understand ADHD.